Key Accessibilities Issues (KAIs) for People with Disabilities (PwDs) at Electric Train Service (ETS) Station - Azmi, Nur Ainaa; Mohd Isa, Haryati; Mohd Nor, Othman; P. Utama, Wahyudi (International Journal of Sustainable Construction Engineering and Technology, 2023)
The establishment of various acts and legislation for PwDs rights signify a strong ethical value and positive support from the government to ensure equal rights for all citizens. It also serves as guidelines for the professional to plan and design their projects. The Malaysian Standard (MS) 1184:2014 for instance contains six KAIs to be considered by the project team during the early planning stage to ensure continuous movement of the PwDs. On the contrary, many researchers reported that Malaysia is still lacking in considering and providing equal accessibility and facilities for this group. This paper aims to investigate whether the provision of KAIs for the PwDs provided at ETS station complies with the MS1184:2014. Three ETS stations in Perak were chosen for the case study. Document analysis of the MS1184:2014 was conducted to identify the KAIs dimensions to be provided for the PwDs at the stations. From the document analysis conducted, an observation checklist was developed to assess the availability and compliance of the KAIs dimensions with the MS1184:2014. The observation was recorded in a tabular method. From the tabulated information, the types and frequency of the availability and compliance of the facilities were determined. The research revealed that although majority of the sub-dimensions/facilities were available at the stations, they do not all comply with the MS. Some of the sub-dimensions/facilities do not function properly and cannot be used by PwDs. The physical barrier or incompliance facilities that were identified throughout the observations could be minimized to give the PwDs accessibility to use the ETS services. Besides, the ETS stations need to provide a more inclusive environment so that the PwDs can be independent and are capable to actively participate with the community. The research also suggested that when it comes to developing or creating better public transportation stations, customer feedback is crucial. The designer or the local authority should be more inventive in designing a barrier-free environment and infrastructure.